126k views
4 votes
Help! logarithmic differentiation

Help! logarithmic differentiation-example-1

1 Answer

7 votes

Recall that we can write


f(x)^(g(x))=e^{\ln f(x)^(g(x))}=e^(g(x)\ln f(x))

so that when we take the derivative, we get by the chain rule


\left(f(x)^(g(x))\right)'=(g(x)\ln f(x))' e^(g(x)\ln f(x))=(g(x)\ln f(x))'f(x)^(g(x))

Here, we have
f(x)=3-\sin2x and
g(x)=\sqrt[3]{x}=x^(1/3). By the product rule,


\left(x^(1/3)\ln(3-\sin2x)\right)'=\left(x^(1/3)\right)\ln(3-\sin2x)+x^(1/3)(\ln(3-\sin2x))'


=\frac13x^(-2/3)\ln(3-\sin2x)+x^(1/3)((3-\sin2x)')/(3-\sin2x)


=\frac13x^(-2/3)\ln(3-\sin2x)+x^(1/3)(2\cos2x)/(\sin2x-3)


=\frac1{3x^(2/3)}\left(\ln(3-\sin2x)+3x(2\cos2x)/(\sin2x-3)\right)


=\frac1{3\sqrt[3]{x^2}}\left(\ln(3-\sin2x)+(6x\cos2x)/(\sin2x-3)\right)

So we have


y'=\frac{(3-\sin2x)^{\sqrt[3]{x}}}{3\sqrt[3]{x^2}}\left(\ln(3-\sin2x)+(6x\cos2x)/(\sin2x-3)\right)

User Atinux
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.